Домашний алтарь Зевса и Геры из загородной усадьбы Херсонеса - Кобелев, А.С.; Яшаева, Т.Ю. (Материалы по археологии, истории и этнографии Таврии, 1996)
В 1981 г. во время раскопок ближней хоры Херсонеса на Гераклейском по- лустрове во дворе усадьбы №93, расположенной на восточном склоне отрога Стрелецкой балки, была найдена рельефная плита из местного сарматского известняка (1, л. 51 In 1981 in the nearest chora of Chersonesos, in the yard of farm 93, a trapeziform plate with a picture of 2 figures was found. Due to some peculiar features one can attribute this relief to Thracian votives of the first centuries A.D. Judging by the composition, iconographie and theme interpretation of the twin portrayal, we can assume that they are Zeus and Gero. Use of lime-stone, crude and slipshod work testify to its local production. However, one should pay attention to original combination of votive relief with family altar. Penetration of Thracian elements to Chersonesos are connected with the stay of Roman legions, many of them were formed of Thracians, and with the influx of people from Minor Asia,Eastern and Danubian provinces of the Roman.